Químio-, régio- e estereosseletividades das reações de Diels-Alder de para-benzoquinonas: um estudo teórico - Servilha, Bruno Moraes (Universidade Federal de São Carlos, 2014)
In this work, some computational theoretical studies on the reactivity of para-benzoquinones and their derivatives in Diels-Alder reactions were proposed These studies were done in order to compliment the corresponding experimental studies ongoing in our laboratory. The Diels-Alder reactions between carbomethoxy-parabenzoquinones 16, 17 e 19 and cyclopentadiene furnished type-A cycloadducts whereas in the corresponding reaction of 18, the B-type cycloadduct was formed. The regiosselectivity of these reactions were rationalized by the comparison of the corresponding transition state energies and the relative stability of the cycloadducts. The presence of a methyl group adjacent to group carbomethoxy in the dienophiles 18 and 19 inhibits the conjugation of these group with the ring systen, and the regiosselectivity on these reactions, at first sight, is not predictable. (CONTINUE)...
chemo-, regio- and stereoselectivities of the Diels-Alder reactions of para-benzoquinones: a theoretical study
Keywords: Química orgânica; Diels-Alder; Estudo teórico; CIENCIAS EXATAS E DA TERRA::QUIMICA